Hot-melt extrusion – filament manufacturing coupled with fused deposition modeling for 3D printed pharmaceuticals -a brief review - Arany, Petra; Vámosi, Bence; Bácskay, Ildikó; Fehér, Pálma (De Remediis, 2025)
3D printing or additive manufacturing are conquering many industrial fields, just as the pharmaceutical industry. There are several types of additive manufacturing processes, however one technology, the fused deposition modeling is outstanding in the pharmaceutical field. Fused deposition modelling uses filaments for printing. These filaments are made out of polymers that has diverse properties, suitable for containing active pharmaceutical ingredients for various usages. These filaments can be produced by hot-melt extrusion process, that the pharmaceutical field already uses for several formulations. In order to get a useable filament, we need more machines than just the extruder. Through the process, the feeder, the conveyor and the winder machines are necessary to get the desired homogeneity, filament diameter, and a ready to use filament roll to easily couple hot melt extrusion with fused deposition modeling. Polymers for pharmaceutical usage are already exists, including polyethylene glycols, polylactic acids, hydroxypropyl cellulose and many more. Finding polymers that has the appropriate rheological properties, heat- and chemical stability to apply in hot-melt extrusion-, and fused deposition modeling process, turned out to be challenging, but not impossible task. In conclusion, hot melt extrusion is a reliable method to produce polymer filaments for fused deposition modeling, that is suitable to print pharmaceuticals, however, the knowledge of this field is continuously expanding, thanks to the researchers around the world.